Pengaruh Pelatihan Sadari Terhadap Pengetahuan,Sikap Dan Deteksi Dini Kanker PayudaraPada Siswi SMK Dwija Dharma Boyolali - Setiawan S, Aan Anies, Yuli Kusumawati, M.Kes (Epid) (2016)
Breast cancer incidence rate is still fairly high and breast cancer is often detected at an advanced stage. The lack of knowledge breast cancer teenager increases the risk of death. The purpose of this study was to determine the effect of training SADARI between knowledge, attitude and how to detected breast cancer female student of SMK Dwija Dharma Boyolali. This research uses an quasi experimental method study design with Separate sample pretest-postest. The population study were female students of SMK Dwija Dharma Boyolali class X 21 Students and class XI 21 students. The sample selection by cluster sampling. Statistically using paired t test. The results showed that there is an effect of training SADARI between knowledge, attitude and how to detected breast cancer (p=0,001) with an incidence of depression in breast cancer patients.